Assertiveness pocketbook, 2nd edition : a pocketful of tips, tools and techniques for those who want to set their own agendas and take control of their lives /: a pocketful of tips, tools and techniques for those who want to set their own agendas and take control of their lives. (©2011) - Unknown
No abstract available